"A gente tinha que se virar sozinha": processos educativos emergentes da andarilhagem de mulheres atletas de futsal - Bianconi, Ana Cláudia (Universidade Federal de São Carlos, 2023)
This research aims to identify, understand and describe the educational processes that emerge from the social practice of wandering among female futsal athletes. To participate in this study, five women futsal athletes who were part of the main team of the club Associação Sãocarlense de Futsal – ASF were selected from records in field diaries of a conversation circle. This is a qualitative research based on dialogicity and centered on subjects, which was developed from interviews with the participants, which were recorded and transcribed in field diaries. For data analysis, we chose to carry out an episodic analysis, in which excerpts from the interviews were selected, presented and discussed, in order to promote reflection around the episodes, associating them, when possible, with Freirean concepts. The results found point to the denunciation of processes of dehumanization and situations of oppression experienced by female futsal athletes when walking as they establish themselves professionally as athletes, and reveal educational processes of coping, mutual care, support, identity, which function as a foundation and contribute to the process of developing critical consciousness that leads to liberating praxis, based on the permanent and constant state of being subjects that they are being.
"We had to fend for ourselves": educational processes emerging from the wanderings of female futsal athletes
Keywords: Futsal de mulheres; Processos educativos; Gênero; Andarilhagem; Humanização; Women's futsal; Educational processes; Gender; Wandering; Humanization; CIENCIAS HUMANAS::EDUCACAO